De dónde viene y a dónde va la animación de la lectura - Sarto, Montserrat (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
From 1974 to the present time. The evolution that has been continued in the reading, and more specifically the encouragement to read. In our country, is evident. The consideration of the responsibility assumed by each one of the social statement, as well as the generation of diverse experiences, have had one of the best stimuli in this author. Nevertheless, as the expounds, the task has still not been completed: it is necessary to continue developing initiatives, really, loving reading and children.